Quality of life after haematopoietic stem cell transplantation in a multiracial population - Bee, P.C.; Gan, G.G.; Sangkar, V.J.; Haris, A.R.; Chin, E. (Malaysian Medical Association, 2011)
Haematopoietic stem cell transplantation (HSCT) was started in Malaysia since 1993 and it has improved the survival of patients with otherwise fatal haematological diseases. This study was initiated because quality of life of these survivors is an important tool in assessing the outcome of this treatment modality. The secondary objective was to identify factors that influenced their quality of life. The European Organization of Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-30) was used to assess the quality of life of eligible patients. A total of 62 patents were recruited. The mean global health score (QoL) was 71.2. The major symptoms faced by our patients were fatigue, financial difficulty and appetite loss. Appetite loss was an independent adverse factor for lower QoL.